GOOGLE CLASSROOM FOR ENGLISH CONVERSATION AT AKADEMI MARITIM NUSANTARA CILACAP - Dhion Meitreya Vidhiasi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2020)
Technology grows every time. Industrial Revolution 4.0 needs everyone to be able to improve including the education area. The teacher must improve their way of teaching since everything is changing. This research attempts to introduce one example of a teaching strategy named blended learning. This strategy needs Google Classroom as the tool of teaching and learning. Descriptive qualitative research is was applied in which the subject was the second semester of Port Management students at Akademi Maritim Nusantara Cilacap. The result showed that even if some students found some difficulties in operating Google Classroom, they were very excited to study via this platform. Furthermore, many advantages can be received by using this platform for teachers and students.